(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In this article the culturological analysis of originality and identity of Turkic nomadic culture is carried out. Historical and culturological and philosophical concepts of domestic and foreign researchers form today social and theoretical outlook of modern Kazakhstan citizens to history and ethnoculture of nomadic society.